Maximizing Mobile Communication Efficiency with Smart Antenna Systems using Beam forming and DOA Algorithms - Ahmed E.Q.; Ameen Z.H.; Al-Mukhtar F.S.; Jaaz Z.A. (Institute of Electrical and Electronics Engineers Inc., 2024)
This study aims to investigate the efficacy of advanced smart antenna systems utilizing beamforming and Direction of Arrival (DOA) algorithms. The primary objective of this research is to explore the potential of these innovative antenna technologies in enhancing the performance of mobile communication networks and optimizing spectrum utilization. By harnessing beamforming algorithms, smart antenna systems can precisely direct their signal emission toward specific users or locations, thereby mitigating interference and multipath effects. This, in turn, leads to improved communication efficiency through heightened signal quality, elevated signal-to-noise ratios (SNR), and expanded coverage areas. The study further seeks to align network architecture, cost considerations, and overall performance to effectively address the escalating requirements of future mobile broadband services. The significance of smart antennas extends beyond mere programmable phase adjustments within an antenna array, as they effectively capitalize on the spatial attributes of available radio resources. This investigation outlines two distinct smart antenna types, outlines the constituent components of an adaptive antenna, and delves into the associated theories, advantages, and limitations of smart antenna deployment. Additionally, the research incorporates a simulation and analysis segment aimed at evaluating the performance of a smart antenna. Through these efforts, the study endeavors to provide comprehensive insights into the potential contributions and novel aspects of employing smart antenna technology in modern communication networks. 2023 IEEE.